The effect of green intellectual capital and carbon emission disclosure on firm size listed on the Indonesia stock exchange in 2019-2021 - Amelia, Refi Nur; Sudibyo, Yvonne Augustine (Technium Business and Management, 2025)
For nearly half a century, global temperatures have increased significantly, and extreme weather events such as cold waves, heat waves, droughts and floods, and natural disasters have been frequent and serious. The purpose of this study was to determine the effect of Green Intellectual Capital and Carbon Emission Disclosure on the Value of Companies listed on the Indonesian Stock Exchange. This research is a quantitative research. This method is also called the discovery method, because with this method various new science and technology can be discovered and developed. This method is called the quantitative method because the research data is in the form of numbers and the analysis uses statistics. The results of the research results show that H1 is accepted, meaning that there is an influence between Green Human Capital on Firm Value. Green Human capital is defined as the ultimate presentation of knowledge, expertise, innovation and the ability of employees to achieve goals. Human capital is inherent in employees, not in the organization, so it can be lost when employees leave the company. These results are supported by previous research conducted by Indrajaya, (2015) that intellectual capital affects firm value as measured by Price to Book Value (PBV). The conclusions of this study are 1. There is a significant and positive effect of Green Human Capital on Firm Size Price to Book Value.